The Influence Of Motivation And Work Environment On The Performance Of Outsourching Employees - Annisa, Hanna; Tukirin, Tukirin (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The purpose of this study was to determine the effect of motivation and work environment on outsourced employee performance. This study uses a survey method. The research variables are motivation and work environment as independent variables, and employee performance as the dependent variable. The research population is outsourced employees, the number of samples is determined by the Slovin formula. The sample selection was carried out by incidental samples. Data collection techniques with questionnaires, and measurement with a Likert scale. Processing techniques and data analysis include descriptive statistical analysis, and multiple linear regression analysis, determining the multiple linear regression model. Based on the results of descriptive statistical analysis, it can be interpreted that motivation (X1), work environment (X2), and employee performance variables (Y) are classified as good. Based on the results of multiple linear regression analysis, a multiple linear regression equation is obtained Ŷ= -0.016 +0.470 X1 + 0.341 X2. From the classical assumption test, the regression shows that the regression model is the Best Linear Unbiased Estimator (BLUE). The adjusted R-square value is 0.759, meaning that the ability to explain the independent variables, namely motivation and work environment on the employee performance variable (Y) is 75.9%, and the remaining 24.1% is explained by other variables not examined. Partially test the hypothesis that the motivational variable (XI) has a significance value of t = 0.000 <0.05, partially having a significant effect on employee performance (Y). Variable X2 has a significance value of t = 0.001 <0.05, which partially has a significant effect on employee performance (Y). Simultaneous hypothesis test results (F test), obtained a significance value of F of 0.000 <0.05, then the motivation variable (XI), work environment (X2) simultaneously has a significant effect on employee performance (Y).